(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
Naproxen, an anti-inflammatory drug, exhibits poor water solubility and flow properties. Spherical agglomerates were prepared by solvent change method. Solvent composition for spherical agglomeration was determined by constructing ternary diagram. Crystallization medium used for spherical agglomerates of naproxen consisted of tetra-hydro-furan (good solvent); water (poor solvent); isopropyl acetate (bridging liquid) in the ratio of 29:61:10, respectively. Spherical agglomerates were characterized by differential scanning calorimetry, infrared spectroscopy, X-ray diffractometry and scanning electron microscopy. Micromeritic and dissolution behavior studies were carried out. Process variables such as amount of bridging liquid, stirring time and duration of stirring were optimized. Dissolution profile of the spherical agglomerates was compared with pure sample and recrystallized sample. Spherical agglomerates exhibited decreased crystallinity and improved micromeritic properties. The dissolution of the spherical agglomerates was not improved compared with pure sample because the dissolution of naproxen dependent on particle size or surface area. Key words: Spherical agglomerates; Naproxen; Crystallinity; Dissolution. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8860 SJPS 2011; 4(1): 1-8